Metagenomic Analysis of the Ferret Fecal Viral Flora - Smits, Saskia L.; Raj, V. Stalin; Oduber, Minoushka D.; Schapendonk, Claudia M. E.; Bodewes, Rogier; Provacia, Lisette; Stittelaar, Koert J.; Osterhaus, Albert D. M. E.; Haagmans, Bart L. (PloS one, 2013)
Ferrets are widely used as a small animal model for a number of viral infections, including influenza A virus and SARS coronavirus. To further analyze the microbiological status of ferrets, their fecal viral flora was studied using a metagenomics approach. Novel viruses from the families Picorna-, Papilloma-, and Anelloviridae as well as known viruses from the families Astro-, Corona-, Parvo-, and Hepeviridae were identified in different ferret cohorts. Ferret kobu- and hepatitis E virus were mainly present in human household ferrets, whereas coronaviruses were found both in household as well as farm ferrets. Our studies illuminate the viral diversity found in ferrets and provide tools to prescreen for newly identified viruses that potentially could influence disease outcome of experimental virus infections in ferrets.